2014
DOI: 10.1186/1477-7819-12-79
|View full text |Cite
|
Sign up to set email alerts
|

A hemangioma of the sigmoid colon mesentery presenting as a retroperitonealtumor: a case report and review

Abstract: Hemangiomas of the gastrointestinal tract and mesentery are uncommon benign vascular lesions. While spontaneous bleeding is the hallmark of the gastrointestinal tumor variant, clinical signs of mesenteric hemangiomas are mostly unspecific. Despite the increasing imaging quality of computerized tomography (CT), in most cases the final diagnosis is established through surgery and histopathologic analysis of a macrobiopsy.We present a case report of a 20-year-old female patient who was admitted with progressive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
0
17
1
4
Order By: Relevance
“…Calci cations were seen scattered throughout the lesion on CT. Some studies suggested that this was due to degenerative changes as a consequence of the thrombosis within the sinuses, caused by perivascular in ammation and stasis of blood ow (4,11). Other studies have shown that calci cations may ultimately form phleboliths, which represent an important diagnostic feature, seen in 26 to 50% of affected adult patients (4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Calci cations were seen scattered throughout the lesion on CT. Some studies suggested that this was due to degenerative changes as a consequence of the thrombosis within the sinuses, caused by perivascular in ammation and stasis of blood ow (4,11). Other studies have shown that calci cations may ultimately form phleboliths, which represent an important diagnostic feature, seen in 26 to 50% of affected adult patients (4).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that this was due to degenerative changes as a consequence of the thrombosis within the sinuses, caused by perivascular in ammation and stasis of blood ow (4,11). Other studies have shown that calci cations may ultimately form phleboliths, which represent an important diagnostic feature, seen in 26 to 50% of affected adult patients (4). Phleboliths are usually signal voided on both Tl and T2 weighted images, and thrombosed vessels show serpiginous structures with high signal intensity on MRI (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In the gastrointestinal tract, hemangiomas only comprise 5-10% of benign tumors with equal distribution between the jejunum and ileum, followed by the large intestine, and stomach. [2][3][4][5] Duodenal hemangiomas are even more rare. More specifically, since 1839, approximately 200 cases of gastrointestinal hemangiomas have been reported with only 15 of those cases involving the mesentery.…”
Section: Introductionmentioning
confidence: 99%